2003
DOI: 10.1111/1539-6924.00350
|View full text |Cite
|
Sign up to set email alerts
|

Trust in Risky Messages: The Role of Prior Attitudes

Abstract: Risk perception researchers have observed a "negativity bias" for hazard-related information. Messages indicating the presence of risk seem to be trusted more than messages indicating the absence of risk, and risk perceptions seem more affected by negative than positive information. Two experiments were conducted to examine alternative explanations of this finding within the area of food additives. Study 1 (N = 235) extended earlier work by (a) unconfounding message valence (positive or negative) from message … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
88
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 27 publications
12
88
1
Order By: Relevance
“…Slovic (1993) provides additional evidence consistent with the asymmetry principle in the context of news events related to the management of a large, local nuclear power plant. More recent evidence supports the asymmetry principle in the context of health dangers (Siegrist and Cvetkovich, 2001) and the food supply industry (Cvetkovich et al, 2002;White et al, 2003).…”
Section: Trust Developmentmentioning
confidence: 83%
“…Slovic (1993) provides additional evidence consistent with the asymmetry principle in the context of news events related to the management of a large, local nuclear power plant. More recent evidence supports the asymmetry principle in the context of health dangers (Siegrist and Cvetkovich, 2001) and the food supply industry (Cvetkovich et al, 2002;White et al, 2003).…”
Section: Trust Developmentmentioning
confidence: 83%
“…Trust in health messages appears to be higher when information is congruent with prior ways of thinking (White et al 2003). The mental models approach to risk communication suggests that risk should be presented using people's health beliefs and understanding of risk as the starting point (Morgan et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We do not think these explanations are relevant in this case because the events reported in the media were actual events, not policy related (e.g., commingling of GM and non-GM crops was found, or evidence was reported that GM foods were harmful) and because the harms were potentially serious (e.g., sickness or death from the consumption of adulterated foods). Another possibility is suggested by White, Pahl, Buehner and Haye (2003) and Poortinga and Pidgeon (2004), who proposed the confirmatory bias hypothesis. In their view the prior beliefs and attitudes of people influence how they react to media events.…”
Section: Public Trust and Risk Perceptionsmentioning
confidence: 98%